Pengaruh Social Media Marketing terhadap Purchase Intention melalui Consumer Brand Engagement: Survei pada Perusahaan GoFood Indonesia - Ahmad Luthfi Hanif (Universitas Kristen Indonesia Toraja, 2025)
The widespread use of Social Media Marketing (SMM) has a significant impact on increasing consumer Purchase Interest (PI). The vast market potential in Indonesia’s Online Food Delivery (OFD) industry can be optimized by GoFood as a food delivery service. This study uses a quantitative method through validity, reliability and hypothesis testing of 208 GoFood user respondents in Jabodetabek which were analyzed using the Partial Least Square Structural Equation Model (PLS-SEM) with SmartPLS 4.0 software. The research findings reveal that SMM content tailored to consumer preferences, such as educational and entertaining content, can enhance consumer engagement in interacting with the brand and the promoted products (CBE). High consumer interaction (CBE) fosters emotional connections that enhance Purchase Intention (PI) for products GoFood offers. As a mediating variable, consumer Brand Engagement (CBE) successfully reinforces the relationship between SMM and PI.